Approaches of family physicians working in primary care regarding palliative care - Nagihan Yıldız Çeltek; Öznur Şahin; Ufuk Ünlü (SERNEV, 2022)
Introduction: Determining the awareness of family physicians working in primary care about palliative care, to determine their attitudes and behaviors towards patients and their relatives, and their approaches are aimed in this study.Methods: The universe of the cross-sectional and descriptive study consists of 194 family physicians in Tokat in January 2020. However 23 physicians who refuse to participate and 15 physicians who could not reached in detected dates were excluded from the study. 156 physicians were applied prepared questionnaire. The necessary permissions were obtained from the Provincial Health Directorate and the clinical research ethics committee. The data were evaluated with IBM Statistics 20.0 SPSS statistical software. Chi-square test was used to test the differences, and p lt;0.05 was accepted statistically significant.Results: Regarding participants 98 (62,8%)were male, 58 (37,2 %) female, mean age 40,5±9,8 and mean working years 15,8. 6.4% (n: 10) of the participants were family medicine specialists and 93.6% (n: 146) general practitioners. The proportion of respondents who state the correct answer as 'palliative care deals with life-threatening diseases' was 60.3%. The proportion of those who helped palliative care patients about nutrition was 29.5% (n: 46) and 60 physicians supported for psychiatric problems (38.5%). 51.3% of the physicians prescribed opioid group drugs. The rate of those who want to follow patients in the family health center as integrated with the palliative care units 20.5%, and this rate was found to be statistically significantly higher in female physicians (p: 0.03). 11.5% of the physicians received palliative care training, while 61.5% stated that they wanted to receive regular training in this regard.26.9 % of participants want to specialize in palliative care. 74.3% of physicians think that palliative care practices should not be included into performance system in the family medicine practices.Conclusions: In the current system, it was found that family physicians did not have sufficient training and equipment related to palliative care. In line with the increasing need for palliative care in primary care, some up-to-date arrangements and in-service trainings should be brought to the agenda.Keywords: Family practice, palliative care, pain, opioid analgesics, palliative care training